Given is the following oscillator $$\ddot{x} + \lambda\dot{x}=x-x^3$$ I've already rewritten this as a system of first order equations $$\begin{cases} \dot{x} = y \\ \dot{y}=x-x^3-\lambda y \end{cases}$$ Now the question is how the Hamiltonfunction $H(x,y)=\frac{1}{2}y^2+U(x)$ changes in time under our given oscillator with $\lambda \in \mathbb{R}$. We know that for $\lambda=0$, $\dot{y}=-U'(x)$. If I calculate $\dot{H}$ I find $$\dot{H}=\frac{\partial H}{\partial x}\frac{\partial x}{\partial t} + \frac{\partial H}{\partial y}\frac{\partial y}{\partial t}=U'(x)\cdot y + y(x-x^3-\lambda y)$$ The problem I face is that I don't know if $U(x)$ depends on $\lambda$. Does anyone have an idea to get me going?


Instead of the Hamiltonian, I can give you the Lagrangian.

In the existence of friction, it is well known to physicists that the following Lagrangian gives the correct equation of motion.

$$L[x,\dot{x},t] = e^{\lambda t/m} \bigg(\frac{1}{2}m\dot{x}^2 - U(x)\bigg)$$

$$\Rightarrow m\ddot{x} +\lambda \dot{x} +U'(x)=0 $$

In your case, $m=1$ and $U(x)=-\frac{1}{2}x^2+\frac{1}{4}x^4$.

You can easily figure out the Hamiltonian.

Otherwise, I would start from defining the first order differential equations in the following way,

\begin{align} e^{\lambda t}\dot{x} &= y \\ e^{-\lambda t} \dot{y} &= x-x^3 \end{align}


IMO it works best to start with the original equation, multiply with $\dot x$, and integrate, identifying the complete derivative expressions. This gets $$ \left[\frac12\dot x^2+\frac14(x^2-1)^2\right]_{t_0}^t=-λ\int_{t_0}^t\dot x(s)^2\,ds. $$ This should tell you what the Hamiltonian is in the case without friction and how the friction term siphons off energy.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.